Training and turnover - Ismail, Hussein Nabil (2016)
Studies exploring the linkages between training and turnover have produced inconsistent results. That inconsistency suggests a path for further study into the variables that might be confounding this relationship. The main purpose of this research was to test the mediating effect of organisational commitment in the relationship between training and turnover intentions. A sample of 124 participants took part in this study. Training was initially found to have a significant inverse relationship with turnover intentions. However, when organisational commitment was entered into the model as a mediating variable, the effect of training on employee turnover intentions became insignificant, suggesting full mediation. The impact of training on turnover intentions is not straightforward, but works first through the effect of training on attitudes, that is on commitment. The results demonstrate the importance of increasing the commitment of employees to the organisation through training, which can help companies to reduce turnover intentions.